Industrial Fabrication of 3D Braided Stretchable Hierarchical Interlocked Fancy‐Yarn Triboelectric Nanogenerator for Self‐Powered Smart Fitness System. Issue 31 (3rd July 2022) - Wu, Ronghui; Liu, Sai; Lin, Zaifu; Zhu, Shuihong; Ma, Liyun; Wang, Zhong Lin
Abstract: Sustainable, clean, random energy resources from the environment, like that from ubiquitous human biomechanical movements, are highly desirable for the information era. Such biomechanical energy can be captured via textile triboelectric nanogenerators (TENGs). However, realizing a textile TENG that has a self‐driven working mode, dynamic pattern designability, high electrical performance, mechanical robustness, and industrialized fabrication is challenging because of the difficulty in fancy‐yarn structure manipulation. Here, for the first time, a 3D braided stretchable hierarchical interlocking fancy‐yarn TENG (3D HIFY‐TENG) with deoxyribonucleic acid‐like double‐wing spiral structure is industrially exploited for multifunctional energy harvesting modes and self‐powered biomechanical sensing. The 3D HIFY‐TENG can generate self‐driven triboelectrical outputs without relying on other objects by body movements. It shows a mechanical robustness (6.9 cN dtex −1 ), excellent stretchability (>350%), weavability, washability and human‐body comfort. Moreover, geometric and mechanical behavior of the 3D HIFY‐TENG are systematically investigated theoretically and experimentally. Further, multifunctional 3D HIFY‐TENG fabrics are explored, which can not only harvest biomechanical energy and monitor body movement, but exhibit a unique adjustable pore effect, providing potential for dynamic electronic textile pattern design. In addition, a smart fitness system is developed for exercise management of real‐time exercise detection, frequency analysis, and self‐powered posture correction alarms. Abstract : A 3D braided stretchable hierarchical interlocking fancy‐yarn triboelectric nanogenerator (3D HIFY‐TENG) with double‐wing spiral structure is industrially exploited for multifunctional energy harvesting modes and self‐powered biomechanical sensing. The self‐driven 3D HIFY‐TENG shows a mechanical robustness, excellent stretchability, weavability, tailorability, washability, and human‐body comfort. With 3D HIFY‐TENG, multifunctional fabrics with a unique adjustable pore effect and a smart fitness system are developed.